Using Discovery Learning and Problem-Based Learning to Increase Students' Motivation for Accomplishment - Suhada, Sitti; Sunardi, Sunardi; Amali, Lanto Ningrayati; Katili, Muhammad Rifai; Lahinta, Agus; Kilo, Juriah R. (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
According to initial observations made during the Basics of Computer Network Engineering and Telecommunications course in class X at TKJ SMK Negeri 5 Gorontalo, students were generally still passive and did not participate much in their education, preferring to listen to what their teachers said. This research aims to analyse: (1) the influence of the Problem Based Learning model on students' achievement motivation; (2) the influence of the Discovery learning model on students' achievement motivation; and (3) differences in achievement motivation between classes treated with Problem Based Learning. This study used a Non-equivalent Control Group Design research design in conjunction with a Quantitative Quasi-Experimental research method. This design consists of two groups that are not randomly selected, then given a pre-test to find out whether there are differences between the experimental group and the control group. The analytical test tool used in testing this research is the Paired Sample T-test with the following test results: (1) The Problem Based Learning model influences students' achievement motivation as indicated by the Sig value; (2) the Discovery Learning model influences students' achievement motivation as indicated by the Sig value (2-tailed) of 0.000 < 0.05. These results show that there are differences in the average achievement motivation of students in classes given the Discovery Learning model; and (3) Apart from that, the independent t test showed that there was no difference in achievement motivation between classes given the Problem Based Learning model and classes given the Discovery Learning model.